Konsep Pengembangan Teknologi pada Health Assistant dengan Menciptakan Holo Buddy Bagi Masyarakat - Jose Manuel Budiman; Vincent v; Calvin Yantson; Novita Chris; Nelson Donglas; Tri Susanti; Elbert Sun (Program Sarjana Sistem Informasi, Universitas Internasional Batam, 2020)
These days people struggle to keep their health, especially in these pandemic days. To keep our health conditions and undergo the health protocol by the Government, we need a technology that can help us keep our health condition, one of it is by avoiding meeting directly (face-to-face) the medical personnel such as doctors and nurses. That is why the society needs Holo Buddy, an AI that uses Machine Learning and Big Data System in keeping human health condition whether it’s physical or mentally. By using Holo Buddy, we hope that this AI (Artificial Intelligence) Hologram Technology can handle these problems and help in keeping our health condition as our own Personal Healthcare Companion. Keywords: Healthcare, Artificial Intelligence, Hologram, Big Data, Machine Learning